Pulsed laser deposition of high-transparency molybdenum oxide thin films - Holovský, Jakub; Horynová, Eva; Horák, Lukáš; Ridzoňová, Katarína; Remeš, Zdeněk; Landová, Lucie; Sharma, Rupendra Kumar (Vacuum, 2021)
Molybdenum oxide is an intensively studied material, thanks to its high bandgap, high work function, and potentially also photochromism, plasmonic properties, and layered structure. In this contribution, we employ Pulsed Laser Deposition (PLD) from stoichiometric MoO3 and metal Mo target at temperature range of 25 °C–500 °C and oxygen pressure variation of 0.1 mbar–0.4 mbar to deposit high transparency MoO3 layers. The combination of Photothermal Deflection Spectroscopy (PDS) and Spectral Ellipsometry is applied to accurately track all the optical properties. The X-ray diffraction and Scanning Electron Microscopy (SEM) are used to monitor crystallinity and surface morphology. We have observed that with increasing temperature, initially amorphous layer becomes smoother and denser, bandgap narrows and sub-gap absorption increases. This trend can be reversed by increasing oxygen pressure. Above 400 °C, the material starts crystallizing, first in monoclinic β-MoO3 phase and then in orthorhombic α-MoO3 phase. The high pressure promotes crystallinity, however increases surface roughness. Depositions form metal Mo target follow the same trends as in the case of stoichiometric MoO3 target, however the deposition from stoichiometric target produces lower sub-gap absorptance. Sub-gap absorptance centred around 1000 nm depends strongly on deposition temperature and weakly on oxygen pressure. -Thin-film molybdenum oxide films prepared by Pulsed Laser Deposition-Optical properties given by combination of Photothermal Deflection Spectroscopy and Ellipsometry-Sub-gap absorptance tracked to find parameter regions of high transparency-Orthorhombic α-MoO3 and monoclinic β-MoO3 films observed at high temperature-Depositions from stochiometric MoO3 target and Mo metal target compared